Knygos ateitis - Fabian, Bernhard (Knygotyra, 2003)
The paper is an inquiry into the nature and future of the book. Owing to its versatility, the book is generally regarded as an all-purpose medium. There can be no doubt that as a medium it performs superlatively well. But it also has serious limitations. These emerged as early as the seventeenth century when the communication of scientific knowledge required a ’faster’ medium than the book and led to the invention of the journal. Similarly, the need to store rearrangeable pieces of information led to the invention of the card index. The need to store large masses of information has revealed further limitations of the book. However, the invention of the computer and the employment of other devices for information storage have not ’invalidated’ the book as a medium. They have merely ’relieved’ the book from functions which it is not ideally suited to perform. In a larger context the book will be reinstated as the medium for the presentation of a coherent argument and for communicating a text in an orderly sequence. The major problem is not the future role of the book, but the continuity of the textual tradition based on the printed book. The digital library which is now under consideration everywhere may establish a disorderly canon of texts, the rationale of which is their availability in electronic form. This would have far-reaching intellectual consequences.